1978
DOI: 10.1128/aem.35.2.269-273.1978
|View full text |Cite
|
Sign up to set email alerts
|

Formation of glycosidases in batch and continuous culture of Bacteroides fragilis

Abstract: Nine strains of Bacteroides fragilis were cultivated in stirred fermentors and tested for their ability to produce glycosidases. B. fragilis subsp. vulgatus B70 was used for optimizing the production of glycosidases. The highest bacterial yield was obtained in proteose peptone-yeast extract medium. The optimum pH for maximal bacterial yield was 7.0, and the optimum temperature for growth was 37°C. The formation of glycosidases was optimal between pH 6.5 and 7.5, and the optimum temperature for synthesis of gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…The activities reported here were detected in crude enzyme preparations under standard assay conditions and higher or other activities may have been measured under optimum conditions. Similarly growth conditions (Berg et al 1978) and substrates (Williams & Withers 1981) affect enzyme levels.…”
Section: Discussionmentioning
confidence: 99%
“…The activities reported here were detected in crude enzyme preparations under standard assay conditions and higher or other activities may have been measured under optimum conditions. Similarly growth conditions (Berg et al 1978) and substrates (Williams & Withers 1981) affect enzyme levels.…”
Section: Discussionmentioning
confidence: 99%
“…SEC was performed on a superose 12 column, using 50 mM ammonium acetate as eluent with a flow rate of 0.4 ml min -1 . Activity for b-glucosidase, a-galactosidase, b-galactosidase and a-Larabinofuranosidase was measured by means of colorimetric assays as described by Berg et al, (1978).…”
Section: Analytical Techniquesmentioning
confidence: 99%
“…A similar finding has been reported in Pseudomonas sp. strain SB-15 (24), which is in contrast to the constitutive a-glucosidase reported in Streptococcus pyogenes (6), Streptococcus mitis 903 (17), and Bacteroides fragilis (2).…”
Section: Discussionmentioning
confidence: 74%
“…The highest level of enzyme production is obtained when both proteose peptone and yeast extract are added to the culture medium. It has been reported that proteose peptone with yeast extract supports the highest yield of oe-glucosidase in B. fragilis (2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation